2018
DOI: 10.1111/jce.13459
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of noninvasive ablation of ventricular tachycardia using high‐intensity focused ultrasound

Abstract: This pilot study suggests that HIFU is potentially useful for noninvasive ablation of targeted, localized myocardial tissues, and it may be potentially applicable for VT ablation, particularly for those with intramyocardial/epicardial origins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In a closed-chest animal model applying a noninvasive HIFU system, as it is clinically used to target human neoplasms 43 , it was shown that with ablation energies of 400W for 2-4 seconds, transmural and localized lesions could be created without apparent injury to skin, lung or pericardium. 44 Yet, thus far no human feasibility studies have been published.…”
Section: High-intensity Focused Ultrasound Evidencementioning
confidence: 99%
“…In a closed-chest animal model applying a noninvasive HIFU system, as it is clinically used to target human neoplasms 43 , it was shown that with ablation energies of 400W for 2-4 seconds, transmural and localized lesions could be created without apparent injury to skin, lung or pericardium. 44 Yet, thus far no human feasibility studies have been published.…”
Section: High-intensity Focused Ultrasound Evidencementioning
confidence: 99%
“…In the last 20 years, investigations into the application of HIFU in the cardiovascular eld have been ongoing, mainly including myocardial ablation and electrophysiological ablation [5][6][7] . Previous studies have established several pathways, including thoracotomy [8] , transthoracic 9 , trans-vascular 10 , and transesophageal 11 . In 2007, Boris Schmidt rst reported the use of a steerable HIFU balloon catheter for radiofrequency ablation (RFA) of the pulmonary vein ostium in patients with atrial brillation, with the success rate of pulmonary vein isolation reaching 89% 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In ophthalmology, the hypotensive effect of high-intensity focused ultrasound (HIFU) in managing intraocular pressure in dogs with primary glaucoma was demonstrated successfully without observing intra-operative complications. [ 26 ] The technique has also been tested with promising results in interventional cardiology strategies such as for managing ventricular arrhythmia,[ 27 28 ] cardiac ablation,[ 29 30 ] and atrial fibrillation treatment. [ 31 32 ] The effectiveness of HIFU in treating drug-resistant hypertension via bilateral renal nerves ablation was investigated in canine models.…”
Section: Introductionmentioning
confidence: 99%